2016
DOI: 10.1002/etc.3246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of activated carbon or biochars on toxicity of different soils contaminated by mixture of native polycyclic aromatic hydrocarbons and heavy metals

Abstract: Activated carbon (AC), biochar from wheat straw (BCS), and biochar from willow (BCW) were added to the soils sampled from areas of strong anthropogenic influence at doses of 0.5%, 1%, 2.5%, or 5% (w/w) and incubated for 2 mo. At the end of this period, the toxicity of the soils was measured. The effect of AC and biochars on the toxicity of the soils varied based on soil, type of amendment, dose, and test organism. For most of the parameters tested, the highest effectiveness of AC in terms of reduction of toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…BET surface area of the biochar was determined to be 281.35 m 2 g -1 . The biochar doses were chosen based on the literature where effective immobilization of contaminants achieved in soil by biochars ( Kiran and Prasad, 2019 ; Kołtowski and Oleszczuk, 2016 ). The biochar levels of 2.5% and 5% were selected in this research.…”
Section: Methodsmentioning
confidence: 99%
“…BET surface area of the biochar was determined to be 281.35 m 2 g -1 . The biochar doses were chosen based on the literature where effective immobilization of contaminants achieved in soil by biochars ( Kiran and Prasad, 2019 ; Kołtowski and Oleszczuk, 2016 ). The biochar levels of 2.5% and 5% were selected in this research.…”
Section: Methodsmentioning
confidence: 99%
“…The average removal efficiency of BbFA in A-CW was up to 99.0 ± 0.23%, which was 10.6 and 1.2% higher than that in the Control and B-CW groups, respectively ( p > 0.05). The results reflected that both AC and biochar promoted the removal of BbFA in CWs, and could be attributed to the immobilization and adsorption of organic contaminants due to their hydrophobic properties . Brennan et al found that the AC has better performance for PAH reduction in porewater than biochar, while the biochar had larger particle sizes.…”
Section: Resultsmentioning
confidence: 93%
“…The results reflected that both AC and biochar promoted the removal of BbFA in CWs, and could be attributed to the immobilization and adsorption of organic contaminants due to their hydrophobic properties. 18 Brennan et al 19 found that the AC has better performance for PAH reduction in porewater than biochar, while the biochar had larger particle sizes.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, oribatid mite communities (which dominate among invertebrates inhabiting the topsoil) display a great variety of responses to heavy metals [23]. Features such as fertility and survival rate of Collembola are mentioned as greatly sensitive indicators of soil contamination with PAHs [24,25]. We also investigated Collembola and Acarina occurrence in soils polluted to various degrees with PAHs [26,27].…”
Section: Introductionmentioning
confidence: 99%